Racial Discrimination during Adolescence Predicts Mental Health Deterioration in Adulthood: Gender Differences among Blacks - Assari, Shervin; Moazen-Zadeh, Ehsan; Caldwell, Cleopatra Howard; Zimmerman, Marc A. (Frontiers in Public Health, 2017)
Background: Despite we already know that racial discrimination has negative mental health consequences, very few studies have used longitudinal design, implemented long term follow up periods, have measured both anxiety and depression, and have explored gender differences. Objective: The current longitudinal study aimed to investigate gender differences in predictive role of change in racial discrimination on deterioration of symptoms of anxiety and depression among Black youth in transition to young adulthood. Methods: Current study followed a non-random sample pf Black youth for 18 years from year 1994 (mean age 15) to year 2012 (mean age 32). All participants were in transition to young adulthood in an economically disadvantaged urban area in the Midwest of the United States. Independent variable was racial discrimination measured in 1999 and 2002. Outcomes were psychological symptoms (anxiety, and depression) measured in 1999 and end of follow up (2012). Covariates included socio-demographics (age, family structure, and parental employment) measured in 1994. Gender was the focal moderator. We used multi-group structural equation modeling while groups were defined based on gender. Results: Multi-group structural equation modeling showed that among male Black youth, an increase in racial discrimination from age 20 to 23 is predictive of increase in symptoms of anxiety and depression from age 20 to age 32. Among female Black youth, increase in racial discrimination was not predictive of change in depressive symptoms. Conclusion: While racial discrimination is associated with negative mental health consequences for both genders, male and female Black youth differ in the effect of an increase in discrimination on deterioration of psychological symptoms. Among those transitioning to young adulthood in economically disadvantaged areas, male Black youth seem to be more susceptible than females to the psychological effects of increased racial discrimination over time.